2012
DOI: 10.1021/ja208720a
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Inhibition of Insulin Fibrillation by a Small Organic Fluorogen with Aggregation-Induced Emission Characteristics

Abstract: Amyloid fibrillation of proteins is associated with a great variety of pathologic conditions. Development of new molecules that can monitor amyloidosis kinetics and inhibit fibril formation is of great diagnostic and therapeutic value. In this work, we have developed a biocompatible molecule that functions as an ex situ monitor and an in situ inhibitor for protein fibrillation, using insulin as a model protein. 1,2-Bis[4-(3-sulfonatopropoxyl)phenyl]-1,2-diphenylethene salt (BSPOTPE) is nonemissive when it is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
321
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 362 publications
(332 citation statements)
references
References 97 publications
5
321
0
3
Order By: Relevance
“…[ 17 ] We termed aggregation-induced emission (AIE) for this novel phenomenon and proposed restriction of intramolecular motions as the main cause for the AIE phenomenon. [ 18 , 19 ] In the past decade, the AIE luminogens have been successfully employed in a variety of biological applications such as for long-term cell tracking, [ 20 ] nonself-quenching DNA labeling, [ 21 ] inhibition of amyloid fi brillation, [ 22 ] monitoring of cell apoptosis, [ 23 ] etc. [ 24 -26 ] The AIE luminogens exhibit high quantum effi ciency, good biocompatibility, and appreciable photostability, which motivate us to further exploit its application in the thriving area of bacteria studies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] We termed aggregation-induced emission (AIE) for this novel phenomenon and proposed restriction of intramolecular motions as the main cause for the AIE phenomenon. [ 18 , 19 ] In the past decade, the AIE luminogens have been successfully employed in a variety of biological applications such as for long-term cell tracking, [ 20 ] nonself-quenching DNA labeling, [ 21 ] inhibition of amyloid fi brillation, [ 22 ] monitoring of cell apoptosis, [ 23 ] etc. [ 24 -26 ] The AIE luminogens exhibit high quantum effi ciency, good biocompatibility, and appreciable photostability, which motivate us to further exploit its application in the thriving area of bacteria studies.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these dyes has given a deeper understanding of protein fibrillation. The approaches used include conventional fluorescence spectra, 26 fluorescence decay, 27 and fluorescence correlation spectroscopy. 28 One of main findings observed in ThT-based experiments was ThT fluorescence intensity showing a sigmoidal function with negligible fluorescence intensity observed in the early stages, gradual increase over time and a plateau in the final stage.…”
mentioning
confidence: 99%
“…Tang and co-workers found that 14 interacted differently with native and fibril insulin, thus leading to different degrees of fluorescence enhancement [26]. The probe 14 cannot bind with native insulin efficiently and remains nonemissive after mixing with native insulin in a buffered solution; however, 14 becomes strongly fluorescent after incubation with insulin fibril.…”
Section: Fluorimetric Biosensors For Biomacromoleculesmentioning
confidence: 99%